Acute-weight-loss strategies for combat sports and applications to Olympic success - Reale, R.; Slater, G.; Burke, L. M. (International Journal of Sports Physiology and Performance, 2017)
It is common for athletes in weight-category sports to try to gain a theoretical advantage by competing in weight divisions that are lower than their day-to-day body mass (BM). Weight loss is achieved not only through chronic strategies (body-fat losses) but also through acute manipulations before weigh-in ("making weight"). Both have performance implications. This review focuses on Olympic combat sports, noting that the varied nature of regulations surrounding the weigh-in procedures, weight requirements, and recovery opportunities in these sports provide opportunity for a wider discussion of factors that can be applied to other weight-category sports. The authors summarize previous literature that has examined the performance effects of weightmaking practices before investigating the physiological nature of these BM losses. Practical recommendations in the form of a decision tree are provided to guide the achievement of acute BM loss while minimizing performance decrements.